Aesthetic Outcomes and Peri-Implant Health of Angled Screw Retained Implant Restorations Compared with Cement Retained Crowns: Medium Term Follow-Up - Livia Nastri; Ludovica Nucci; Vincenzo Grassia; Rino Miraldi (Journal of Functional Biomaterials, 2021)
Single tooth implant restorations in the aesthetic area are a demanding challenge. If a complete osseointegration is mandatory, the final result has to result in a higher standard of biomimetic and soft tissue health among natural teeth. This outcome is traditionally pursued by cementing crowns over individualized abutments. However, in recent years, the need for controlling peri-implant health and the preference towards a retrievable solution has led to an increase in screw-retained crowns, which is not always applicable when the implant axis is not ideal. In the aesthetic area, the use of a novel technical solution represented by the angled screw channel (ASC) of the abutment has been proposed in order to match the advantages of the screwed solution with the aesthetic demands. The aim of this study was to compare ASC crowns to cemented crowns (CC) in single implant restorations using the white esthetic score (WES) and pink esthetic score (PES) at the crown delivery and at a follow-up of a minimum of 2 years. Peri-implant health and marginal bone loss (MBL) were also evaluated. The mean follow-up was 44.3 months, with a mean MBL of 0.22 mm in the ASC group and 0.29 mm in the CC group. The total WES/PES score was 16.6 for ASC, compared with 17.3 for CC at baseline, and 16.2 and 17.1, respectively, at follow-up. Both of the groups reached a high WES/PES, and this was maintained over time, without signs of peri-implant diseases or bone loss, regardless of the choice of connection. In conclusion, ASC can be adopted in cases where the implant axis is not ideal, with aesthetic and functional results that are comparable to implants restored by cemented crowns.